IMPACT OF INFORMATION TECHNOLOGY ON SALES PERFORMANCE OF HOTELS - Tumusiime Desire Elvis (UCU, 2024)
The impact of Information Technology (IT) on sales performance of hotels is examined in this dissertation, with a particular focus on hotels in Kampala District. As a student of Culture and Society, with a specialization in Tourism and Hospitality Management, I undertook extensive research on how IT advancements influence operational efficiency and customer satisfaction, which in return affected sales results .The study analyzed both qualitative and quantitative methods, with data gathered from various hotels in Kampala. The findings demonstrated a significant correlation between the adoptions of advanced IT systems and improved sales performance, suggesting that hotels adapted to technology for marketing, reservations, and customer relationship management see enhanced revenue generation and customer retention. My academic journey of pursuing a Bachelor of Tourism and Hospitality management from Uganda Christian University while attaining training from different areas has given me the understanding I need to comprehend the complex dynamics of sales performance in the hospitality industry taking into account both the operational and customer facing aspect of hotel management This study has added to the body of knowledge in the field of tourism and hospitality management by providing industry practitioners with useful suggestions for boosting sales through the implementation of Strategic IT.
The dissertation investigates the influence of Information Technology (IT) on the sales performance of hotels in Kampala District in Uganda. The study focuses on how IT system like reservation platforms, customer relation management (CRM) tools and marketing technologies enable operational effectively ,improve customer satisfaction and leads to sales growth. By using quantitative research method, the study assessed the level of IT adoption in the hospitality sector and its both direct and indirect effect on sales performance. The finding of this research are intended to guide hotel managers in developing strategies that leverage IT to boost sales enable customer service and maintain a competitive edge in the market .The study contributes to the growing body of knowledge on IT in the tourism and hospitality sector offering practical recommendations for improving sales performance through the changing technology.